Pre-harvest sprouting tolerance in hard white winter wheat - Pisipati, Sudha R. (Kansas State University, 2008)
In many countries producers have been growing varieties of hard white winter (HWW) wheat since decades. The cause of concern is most varieties of HWW wheat are susceptible to pre-harvest sprouting (PHS) which affects grain quality. Environmental conditions like high humidity, precipitation, heavy dew and hormonal activity at physiological maturity stimulate PHS in HWW. To alleviate these conditions research was carried out at KSU. KS01HW163-4, a sprouting tolerance line was crossed with Heyne, a sprout susceptible cultivar. A total of 224 doubled haploid (DH) lines thus produced were phenotyped in the present study through experiments conducted in controlled environments. The objectives of this research were to (i) characterize and phenotype the doubled haploid lines for PHS in controlled environments; (ii) understand the impact of growth environment (high temperature and/or drought) and; (iii) impact of exogenous application of growth hormones on tolerance to pre-harvest sprouting in the parental lines of the doubled haploid population. The phenotypic data collected from this research will be ultimately combined with the genotypic data to identify DNA markers related to PHS tolerance and provide DNA markers for marker assisted selection. Based on my results of the germination percentages from the 224 DH lines, the population was distributed as susceptible, and tolerant to PHS showing a bimodal distribution and X[superscript]2 analysis indicating a complimentary gene action. From the study of the influence of environmental factors on PHS, my results confirmed a definite influence of stress on sprouting. Under optimum temperature (OT), KS01HS163-4 was tolerant to PHS, but at HT and/or drought it became susceptible to PHS. Growth under stressed conditions changed the tolerance levels to PHS. Seed dry-weight, and harvest index were also influenced negatively due to stress. Therefore multi-location tests must be conducted with variable environments to test the stability of a variety to PHS. From the study of the influence of phytohormones on PHS, the results suggest that tolerance to sprouting was seen in seeds from plants sprayed with abscisic acid (ABA) and paclobutrazol (GA-inhibitor) treatments where as those from gibberellic acid (GA) treatment showed susceptibility to sprouting.
Keywords: Hard white winter wheat; Preharvest sprouting tolerance; Heat/Drought stress; Gibberellic Acid (GA); Abscisic Acid (ABA); Phytohormone; Agriculture, Agronomy (0285); Agriculture, General (0473); Biology, Plant Physiology (0817)